Reverse and Green Logistics Implementation for Sewage Treatment Plant Installation of “BELLA” Apartment Building - Rivaldy, M. Labib; Dian Sua Pratama, Bayu (Journal of World Science, 2023)
Industrial and household operations mostly produce liquid waste that can harm the environment without further processing or processing. "Bella" Apartment is an apartment building located in one of the big cities in Indonesia, called Surabaya. The waste generated from this building comes from household activities such as toilet waste, laundry waste and kitchen waste. The purpose of this study is to minimize costs and increase the income of business owner.  This study used a qualitative descriptive method with 3 informants.  Based on financial analysis over the past 12 months, the management often complains about the high consumption of water so that the total cost of water paid to the water provider becomes higher and the owner's concern for the environment. water used in public facilities is taken from water sources for washing vehicles, washing clothes and other activities. In this study, the design of the Sewage Treatment Plant will be carried out, calculating the installation costs, the savings that can be obtained so that it can increase revenue, how to process secondary waste and maintenance from the sewage treatment plant, and the implementation of the Reverse Logistics concept in handling waste.  Reduce the amount of operating costs from electricity and Water costs to increase revenue.